On the Role of sIL-2R Measurements in Rheumatoid Arthritis and Cancers - Anna Maria Witkowska (Mediators of Inflammation)
A soluble IL-2 receptor (sIL-2R) is a circulating form of a membrane receptor localized on lymphoid and some cancer cells. The biological function of sIL-2R has not been completely understood. Substantially, it seems to reflect T-lymphocyte activation in diseases of different pathology. Moreover, the soluble receptor has been considered, at least in part, responsible for unsuccessful immunotherapy with IL-2 in cancers. Several lines of evidence indicate sIL-2R measurements to be useful in determining disease progress and prognosis. This review summarizes current knowledge on the sIL-2R behavior in RA and solid cancers of varied etiology.